Statins and Nitric Oxide Donors Affect Thrombospondin 1-Induced Chemotaxis. (October 2014) - Seymour, Keri; Stein, Jeffrey; Han, Xuan; Maier, Kristopher G.; Gahtan, Vivian
Background: Thrombospondin 1 (TSP-1) induces vascular smooth muscle cell (VSMC) migration and intimal hyperplasia. Statins and nitric oxide (NO) donors decrease intimal hyperplasia. We previously showed that statins (long-term exposure) and NO donors inhibit TSP-1-induced VSMC chemotaxis.Hypotheses: (1) Pretreatment with short-term statin will inhibit TSP-1-induced VSMC chemotaxis and (2) NO donors will enhance statin inhibition of TSP-1-induced or platelet-derived growth factor (PDGF)-induced VSMC chemotaxis. Methods: We examined these treatment effects on TSP-1-induced VSMC chemotaxis: (1) long-term (20 hours) versus short-term (20 minutes) pravastatin, (2) diethylenetriamine NONOate (DETA/NO) or S-nitroso-N-acetylpenicillamine (SNAP) in combination with pravastatin, and (3) comparison of TSP-1 to PDGF as a chemoattractant. Results: Pravastatin (long term or short term) inhibited TSP-1-induced chemotaxis. Diethylenetriamine NONOate and SNAP impeded statin inhibition of TSP-1-induced chemotaxis. Platelet-derived growth factor and TSP-1 had opposite effects on DETA/NO-pravastatin treatment. Conclusion: Short-term statin pretreatment inhibited TSP-1-induced VSMC chemotaxis, suggesting a pleiotropic effect. High-dose NO reversed statin inhibition of TSP-1-induced chemotaxis, suggesting NO and statin combination therapies warrant further study.